Bullying es a Cause of Funtional Neurological Disorders (Conversion Disorder): a Case Report (London Journal of Medical and Health Research, 2024)
The conversion disorder, today called functional neurological disorder is a highly disabling condition both physically and mentally, which affects children simulating various diseases of the nervous system in its motor, sensitive or sensory components, difficult to diagnose, due to different causes with a prolonged evolution and generally causes social isolation in children; the neurofunctional picture requires for diagnosis using numerous medical tests with a high cost and burden for the health system that was previously done by ruling out. Bullying or school bullying is characterized by violence between peers at school, in which there is one or more bullies against the victim, using various types of violence, whether physical, emotional, psychological, and more recently cyberbullying, causing various traumas in the victim, sometimes with serious consequences for their health. In the present case, we describe a girl who was hospitalized due to highly disabling pain in the spine and lower limbs, which prevented her from sitting and walking, to which paresthesias were later added, which began after a traumatic accident. After several studies that ruled out an organic cause of the symptoms and their improvement with a placebo, a diagnosis of functional neurological disorder was made, which was later proven to have been caused by the stress of the bullying of whisch she was a victim.
Keywords: type 2 diabetes mellitus; diabetic nephropathy; P-selectin (CD62P); E-selectin (CD62E); kidney tissue biopsy; microvascular complications.; Hemodialysis; validation; Chronic kidney disease; Health-related quality of life; bolivia; latin america; Cross-cultural adaptation; patient outcomes; renal replacement therapy.; Surgery; Child; fracture; pelvic; acetabular; Bullying; conversion disorders; funcional neurological disorders.